2014
DOI: 10.1002/dev.21231
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the HPA and HPG axes in the context of early life adversity in incarcerated male adolescents

Abstract: The effects of early life adversity can be observed across the lifespan, and the Hypothalamic-Pituitary-Adrenal (HPA) and Hypothalamic-Pituitary-Gonadal (HPG) axes could be mechanistic intermediaries underlying this phenomenon. The current study examined fifty adolescent males aged 12–18 in a maximum-security correctional and treatment setting. Saliva samples were collected five times a day for two day and assayed for cortisol, testosterone and DHEA. Youth completed semi-structured life stress interviews and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 92 publications
3
40
0
Order By: Relevance
“…It would be even more informative, however, to examine the degree of coordination among multiple hormones. Studies examining within-adolescent associations between cortisol and testosterone responses reported positive coupling for adolescents (Marceau et al, 2013;Dismukes et al, 2014;Johnson et al, 2014;Marceau et al, 2014). The present findings suggest that during the different phases of a social-evaluative situation, cortisol and testosterone also show coordinated activation in adult men, in pre/early pubertal boys, and in pre/early pubertal girls, suggesting that coupling is not specific to adolescence.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…It would be even more informative, however, to examine the degree of coordination among multiple hormones. Studies examining within-adolescent associations between cortisol and testosterone responses reported positive coupling for adolescents (Marceau et al, 2013;Dismukes et al, 2014;Johnson et al, 2014;Marceau et al, 2014). The present findings suggest that during the different phases of a social-evaluative situation, cortisol and testosterone also show coordinated activation in adult men, in pre/early pubertal boys, and in pre/early pubertal girls, suggesting that coupling is not specific to adolescence.…”
Section: Discussionmentioning
confidence: 43%
“…However, as proposed by Dismukes et al (2014), the overlap in the top-down processes of the two axes may result in their parallel activation and deactivation in a coordinated fashion. It is possible that this kind of coordination occurs only in certain situations or only when a situation is appraised in a certain way.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The investigations converge on the use of sophisticated statistics to capture within-individual hormone processes (see especially (Marceau, et al, 2013)); on a practical level, these statistical models can be easily used within a broad range of archival studies which have measured multiple biomarkers but which have analyzed them in isolation. The Life History model’s prediction that HPA-HPG axis interplay would be shaped by early stress exposure was clearly supported in one study (Dismukes, et al, 2014), but a nuanced picture was more typical. For example, Ruttle and colleagues (Ruttle, et al, 2013) found tight HPA-HPG coupling within early adolescents, but found an early longitudinal switch to an adult-like pattern within those with early life stress (Ruttle, et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, the HPA and HPG axes could be intermediary mechanisms underlying the life adversity symptoms observed in patients with PTSD. Dismukes et al (2015) reported that coupling of the HPA and HPG axes can be observed in incarcerated adolescents, particularly in those with the greatest life stresses.…”
Section: Introductionmentioning
confidence: 99%